2013
DOI: 10.1016/j.nbd.2012.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Limited regional cerebellar dysfunction induces focal dystonia in mice

Abstract: Dystonia is a complex neurological syndrome broadly characterized by involuntary twisting movements and abnormal postures. The anatomical distribution of the motor symptoms varies among dystonia patients and can range from focal, involving an isolated part of the body, to generalized, involving many body parts. Functional imaging studies of both focal and generalized dystonia in humans often implicate the cerebellum suggesting that similar pathological processes may underlie both. To test this, we exploited to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 55 publications
6
75
0
Order By: Relevance
“…We have previously shown that restricting the tottering mouse genotype to PCs causes ataxia and episodic dystonia, similar to the phenotype observed in tottering mice (Raike et al, 2012). Additionally, selective postnatal knockdown of Cacna1a in PCs using L7-Cre also caused overt motor defects.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…We have previously shown that restricting the tottering mouse genotype to PCs causes ataxia and episodic dystonia, similar to the phenotype observed in tottering mice (Raike et al, 2012). Additionally, selective postnatal knockdown of Cacna1a in PCs using L7-Cre also caused overt motor defects.…”
Section: Discussionsupporting
confidence: 66%
“…Though Cacna1a is most abundantly expressed in cerebellum, other brain regions relevant for movement such as motor cortex and basal ganglia show expression as well (Lein et al, 2007). This scenario cannot be ruled out, but is not supported by data from other Cacna1a mutants where cerebellar circuitry is specifically implicated in behavioral dysfunction (Campbell et al, 1999, Walter et al, 2006, Raike et al, 2012). Fourth, the dysfunctional signaling occurs downstream of GCs and PCs in deep cerebellar nuclei, which also express Ca V 2.1 channels.…”
Section: Discussionmentioning
confidence: 93%
“…Clinical and experimental studies of secondary dystonia strongly implicate forebrain dysfunction as a cause of dystonia (49,50), but several hindbrain elements have also been implicated (51)(52)(53)(54). Taking advantage of different Cre-expressing lines, we began to explore which brain regions are sufficient to mimic the behavioral abnormalities of N-SKI mice.…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…Motor behavioral effects of different stimulation parameters were also assessed using a semi-quantitative scoring system adapted from prior nonhuman primate, porcine and rodent studies [30][31][32][33][34]. Prior to these experiments, the maximal tolerable stimulation amplitude was determined for each DBS lead contact for each animal by a consensus of the veterinary and scientist team.…”
Section: Motor Behavior Assessmentsmentioning
confidence: 99%